INCREASING TEACHERS' CAPABILITIES IN ONLINE LEARNING BY USING WHATSAPP DURING THE PANDEMIC AT SDN 18 BENGKALIS - Kamaruddin (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
Organizing online learning for each educational unit and determining how to deliver learning to students can be done using social media. Choosing social media for learning is necessary because it transcends space and time, making communication with distant people easier. Therefore, it was important to train teachers in using WhatsApp as an alternative for learning through action research or school action research methods. This study involved 8 teachers at SDN 18 Bengkalis. The results showed that in Cycle I, teachers’ understanding of online learning reached an average of 51.13 in the sufficient category. After improvements and reflection from the first cycle, Cycle II showed an average of 73.13 in the good category. Teachers’ ability in learning during Cycle I was categorized as sufficient, while in Cycle II, 2 teachers reached the very good category and 6 teachers reached the good category. The study concluded that teachers’ ability in using WhatsApp for explaining, guiding, and assigning tasks improved from Cycle I to Cycle II.